THE RELATIONSHIP OF HEALTH CONTENT ON TIKTOK ON HEALTHY LIVING BEHAVIORS AMONG YOUNG PEOPLE IN BIREUEN CITY - Eka Lestari Sitepu; Anggi Pramono; Hernia Novianti (PT. Radja Intercontinental Publishing, 2026)
The development of information technology is changing the information consumption patterns of the younger generation, withTikTok becoming the most popular short video platform in Indonesia, with 194.37 million users by 2025. Health content on TikTokhas the potential to influence healthy lifestyles post-COVID-19. The purpose of this study was to measure the relationship betweenhealth content on TikTok and healthy lifestyles among young people in Bireuen City. The research methodology used a cross-sectional study of 70 young people in Bireuen City. Chi-square analysis with a p-value <0.05 was used to determine the influence or significance of variables. The data analysis used SPSS 27.0. The results showed that the majority of respondents were female (58.6%),with 64.3% aged 21-25 years old, and 71.4% of respondents spent daily time using TikTok. Bivariate analysis found a significant relationship between gender and healthy lifestyle behaviors (p-value = 0.11), and a significant relationship between duration and healthy lifestyle behaviors (p-value = 0.003). TikTok content effectively increases health awareness through the FYP algorithm, especially among older adults and for longer durations. TikTok health content has a positive influence on healthy lifestyle behaviors, depending on digital literacy and content quality. Therefore, evidence-based educational strategies are needed to minimize risks.